Discourse and 'democracy': some signals from the South African corpus of English - Robert de Beaugrande; Linda Pearce Williams (Revista Brasileira de Linguística Aplicada, 2002)
Public discourse is replete with terms whose meaning is contested in the service of competing ideologies. In the discourse of the 'new' South Africa, as attested by a recently compiled corpus, the term 'democracy' is found to represent at least three conceptions: (1) a doctrine of equality in human rights and in personal and civil liberties; ( 2 ) a political system of 'majority rule' by means of a secure electoral machinery with multiple parties and universal voting rights; and (3) an economic system of free enterprise and equal opportunity in the economy and the job market. These are plainly incompatible, and, as the data show, the third one is currently undermining the first. O discurso público é repleto de termos cujos múltiplos significados divergem em função de estarem a serviço de diferentes ideologias. No discurso da "nova África do Sul", como comprovado no corpus recolhido recentemente, o temo "democracia" pode representar pelo menos três concepções: (1) uma doutrina de igualdade nos direitos humanos e nas liberdades civis e pessoais; (2) um sistema de "norma de maioria" através de uma engenharia eleitoral segura com múltiplos partidos e direitos universais de voto; e (3) um sistema de empresas livres e igualdade de oportunidades na economia e no mercado de trabalho. Estas concepções são totalmente incompatíveis, e, como os dados demonstram, a terceira idéia está destruindo a primeira.